Estudo ecológico e análise espacial da hanseníase no estado do Ceará - Montenegro, Ana Claudia Dorta (2002)
This research aims at studying hanseniasis, ancient disease which is a serious public health affair in Brazil and, particularly in Ceará. Cases detection in this state have being arising and the highest indexes can be noticed in possible focus of the disease. Therefore, the influence of some specific factors such as social, economical, demographical, and environmental have been studied in the distribution of this disease in Ceará through a descriptive study of the ecological type. Data related to the disease have been used (average of the incidence index between 1991 and 1999 concerning the cities in the state) and, information from IBGE, Human Brazilian Development Atlas, IPLANCE (Planning Institute of Ceará) e FUNCEME (Meteorology Foundation of Ceará). Initially, a linear regression analysis has been done, through Stata Software. Following, the spatial analysis of the data has been used in order to investigate the existence of spatial dependence of the outcome variable. Decomposition of spatial variable has been done in wide and narrow scale. In order to measure the variation of the hanseniasis index in a wide scale, the patterns responsible for the data analysis have been used. The variation in a narrow scale have been evaluated considering the index I by Moran, which pointed the existence of spatial autocorrelation. The spatial analysis has been done by using Arcview 3.1, S-Plus 2000 and S+Spatialstats softwares.